Empowering Banyuraden Village through Strengthening Product Brand Image: Penguatan Brand Image Produk sebagai Upaya Pemberdayaan Desa Banyuraden - Rukmini, Ambar; Pujimulyani, Dwiyati; Titin Laswati, Dyah; Sri Utami, Kristiana (Universitas Lancang Kuning, 2025)
This article aims to describe the role of the Village Empowerment Team (Tim Pemberdayaan Desa Binaan = PDB) in efforts to empower Banyuraden Village, Sleman Regency, DIY through strengthening product’ brand image. Until now, the village has not had a product that can be a village characteristic. In fact, there has been a product produced since the seventies, namely lapis legit. Efforts to brand the product are carried out by increasing understanding of brand image, implementing controlled production, redesigning packaging, marketing strategies, and managing sustainable businesses. The results of this activity show an increase in business actors' awareness of the importance of brand image in attracting consumers and expanding the market. Strengthening brand image is expected to not only increase sales, but also create a distinctive identity for village products that can be an attraction in a wider market. Through this activity, strengthening product’ brand image has proven to be one of the effective steps in empowering village communities, increasing economic independence, and developing local potential more optimally.